Enlarged anterior cranial fossa and restricted posterior cranial fossa, the disproportionate growth of basicranium in Crouzon syndrome. Issue 9 (September 2019) - Lu, Xiaona; Forte, Antonio Jorge; Steinbacher, Derek M.; Alperovich, Michael; Alonso, Nivaldo; Persing, John A.
Abstract: Crouzon syndrome patients develop normal intracranial volume and potential restricted posterior cranial fossa volume with growth. This study aims to trace the segmental anterior, middle and posterior cranial fossae volume, and structural morphology in these patients, in order to help discern more focused and individualized surgical treatment plan. Ninety-two preoperative CT scans (Crouzon, n = 36; control, n = 56) were included, and divided into 5 age related subgroups. CT scans were measured using Mimics and 3-matics software. Overall, Crouzon syndrome patients grew to a 27% (p = 0.011) increased anterior cranial fossa volume and a 20% (p = 0.001) decreased posterior cranial fossa volume, with normal middle cranial fossa and entire intracranial volume measurement. The posterior cranial fossa of Crouzon syndrome initially developed significantly reduced volume (19%, p = 0.032), compared to normals, from 6 months of age, and remained reduced thereafter. The 7.63 mm shortening of posterior cranial fossa length contributed most to the shortened entire cranial length (9.30 mm, p = 0.046). Although the entire cranial volume of Crouzon syndrome is normal overall, the segmental anterior, middle and posterior cranial fossae developed disproportionately. The early significant and lifelong restricted posterior cranial fossa addresses the importance of early posterior cranial expansion. Ideally expansion would have vectors in all three dimensions.